Molecular determinants dictating cell surface expression of the human sodium-dependent vitamin C transporter-2 in human liver cells - Subramanian, Veedamali S. (American Physiological Society, 2010)
The human sodium-dependent vitamin C transporter-2 (hSVCT2) plays an important role in cellular accumulation of ascorbic acid in liver cells. However, little is known about the molecular determinants that direct hSVCT2 to the cell surface in hepatocytes. We addressed this issue using live cell imaging methods to resolve the distribution and trafficking of truncated or mutated hSVCT2 constructs in a cellular model of human hepatocytes, HepG2 cells. Whereas a full-length hSVCT2-yellow fluorescent protein (YFP) fusion protein was functionally expressed at the cell surface in HepG2 cells, serial truncation and mutation analysis demonstrated an essential role for both NH(2)- and COOH-terminal sequence(s) for cell surface expression and function. Video-rate confocal imaging showed evidence of dynamic hSVCT2-YFP containing intracellular trafficking vesicles, the motility of which was impaired following disruption of microtubules using nocodazole. However, in a HepG2 cell line stably expressing hSVCT2-YFP at the cell surface, plasma membrane levels of hSVCT2 were unaffected by inhibition of microtubule-associated motor proteins; rather, surface expression of hSVCT2-YFP was increased following treatment with myosin inhibitors. Together, these results show that 1) both NH(2)- and COOH-terminal sequences are essential for proper localization of hSVCT2, 2) cell surface delivery is dependent on intact microtubules, and 3) peripheral microfilaments regulate insertion and retrieval of hSVCT2 into the plasma membrane.